Hedonic prices indexes for new passenger cars in Portugal (1997-2001) - Reis, Hugo J. (2022)
In this paper we study the e¤ects of quality change on the price index for new passenger cars in Portugal for the years 1997-2001. Hedonic regression models are studied, giving particular emphasis to the relation between the form of the price index and the speci¤cation of the hedonic equation and estimation method used. The results indicate that the CPI component corresponding to this item may have been overestimated by as much as 2:2 percentage points per year. This corresponds to an overestimation of the overall CPI by about 0:15 percentage points per year. As a by-product of this analysis it is also possible to conclude that the quality of new cars sold in Portugal increased on average 4:8 percent per year during this period.